Cyberbullying and the Gifted: Considerations for Social and Emotional Development. Issue 3 (July 2018) - MacFarlane, Bronwyn; Mina, Keri
The use of technology can promote learning, higher-order thinking, deeper understanding, collaboration, and student engagement. But if unchecked and unfacilitated, online cyberbullying can become an impediment to learning and threaten young people's sense of well-being. Cyberbullying is a type of youth aggression that teachers and parents must consider how to integrate technology for educational purposes and decrease online bullying scenarios with targeted instruction and strategies in an online culture. This article examines cyberbullying and relevant concerns to educating high-ability students. Motivation will be discussed with suggestions, resources, and considerations for working with high-ability young people in developing their social–emotional awareness and strategies for addressing bullying.